Multiple genetic variants involved in both autoimmunity and autoinflammation detected in Chinese patients with sporadic Meniere's disease: a preliminary study - Zou, Jing; Zhang, Guoping; Li, Hongbin; Zhao, Zikai; Zhang, Qing; Pyykkö, Ilmari; Mäkitie, Antti (Frontiers in Neurology, 2023)
Background The mechanisms of Meniere's disease (MD) remain largely unknown. The purpose of this study was to identify possible genetic variants associated with immune regulation in MD. Methods The whole immune genome of 16 Chinese patients diagnosed with sporadic MD was sequenced using next-generation sequencing. Results Definite pathological variants of MEFV (c.1223G>A, c.1105C>T), COL7A1 (c.5287C>T), and ADA (c.445C>T) contributing to the clinical phenotype were found in three patients. Limited and likely pathological variants of TLR3 (c.2228G>A) and RAB27A (c.560G>A) were detected in one patient each. The following definite pathological variants impairing the structure and function of translated proteins were detected in 10 patients, and multigene variants occurred in five patients: PRF1 (c.710C>A), UNC13D (c.1228A>C), COLEC11 (c.169C>T), RAG2 (c.200G>C), BLM (c.1937G>T), RNF31 (c.2533G>A), FAT4 (c.11498A>G), PEPD (c.788A>G), TNFSF12 (c.470G>A), VPS13B (c.11972A>T), TNFRSF13B (c.226G>A), ERCC6L2 (c.4613A>G), TLR3 (c.2228G>A), ADA (c.445C>T), PEPD (c.151G>A), and MOGS (c.2470G>A). The following limited pathological variants impairing the structure and function of translated proteins were detected in five patients, with double gene variants identified in one patient: EXTL3 (c.1396G>A), MTHFD1 (c.2057G>A), FANCA (c.2039T>C), LPIN2 (c.1814C>T), NBAS (c.4049T>C), and FCN3 (c.734G>A). Conclusion Patients with sporadic MD carry multiple genetic variants involved in multiple steps of immune regulation, which might render patients susceptible to developing inflammation via both autoimmune and autoinflammation mechanisms upon internal stress.